Neutrophil chemokines and their role in IL-18-mediated increase in neutrophil O(2)(−) production and intestinal edema following alcohol intoxication and burn injury - Akhtar, Suhail (American Physiological Society, 2009)
We examined the role of interleukin (IL)-18 and cytokine-induced neutrophil chemokines (CINC)-1 and CINC-3 in the neutrophil release of superoxide anion (O(2)(−)) and elastase following alcohol/ethanol (EtOH) and burn injury. Male rats (∼250 g) were gavaged with EtOH to achieve a blood EtOH level of ∼100 mg/dl before ∼12.5% total body surface area burn or sham injury. Immediately after injury, rats were administered with anti-rat IL-18 antibody (80 μg/kg) or isotype control. After 20 min, anti-IL-18 antibody-treated rats were given either recombinant (r) rat CINC-1 or CINC-3. On day 1 after injury, the combined insult of EtOH and burn injury caused a significant increase in neutrophil elastase and O(2)(−) production as well as an increase in neutrophil accumulation, myeloperoxidase activity, and edema in the intestine. Treatment of rats with anti-IL-18 antibody normalized the above parameters. However, administration of rCINC-1 in anti-IL-18 antibody-treated rats increased the above parameters to levels similar to those observed following EtOH and burn injury. In contrast, administration of rCINC-3 did not influence the above parameters except neutrophil elastase. These findings indicate that IL-18 and CINC-1 may independently modulate neutrophil tissue-damaging actions following EtOH and burn injury. However, the finding that the treatment of rats with anti-IL-18 antibodies inhibits CINC-1 and CINC-3 supports the notion that IL-18 plays a critical role in increased neutrophil tissue-damaging action following a combined insult of EtOH intoxication and burn injury.